Titanium implant loaded with paeoniflorin liposome and preparation method thereof
By preparing a porous structure on the surface of a titanium implant and loading it with paeoniflorin liposomes, the problems of postoperative inflammation and delayed osseointegration of titanium implants were solved, and the efficiency of anti-inflammatory and osseointegration was improved.
Patent Information
- Application Number
- CN202511098503.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-06
- Publication Date
- 2025-11-14
AI Technical Summary
Titanium implants are prone to causing acute inflammatory reactions and delayed bone integration after surgery. Existing relief measures have not effectively solved problems such as low drug utilization, insufficient local concentration, or sudden release.
Porous titanium sheets were prepared by anodizing, acid etching and oxygen plasma treatment. Combined with dopamine and liposome technology, paeoniflorin liposomes were loaded onto the surface of the titanium implant. The liposome nanocarriers protected paeoniflorin and achieved directional and timed release.
It significantly improved the anti-inflammatory effect and bone integration efficiency of titanium implants, enhanced drug utilization, protected the stability of paeoniflorin under physiological conditions, and achieved targeted release.
Smart Images

Figure CN120939305A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomaterials technology, specifically to a titanium implant loaded with paeoniflorin liposomes and its preparation method. Background Technology
[0002] With the widespread application of orthopedic implant materials, titanium and its alloys have become the mainstream choice due to their excellent mechanical properties and biocompatibility. However, titanium implants are prone to causing acute inflammatory reactions and delayed osseointegration postoperatively, leading to an increased risk of implantation failure. Currently, systemic drug administration or surface modification techniques are commonly used in clinical practice to alleviate inflammation, but these methods suffer from problems such as low drug utilization, insufficient local concentration, or burst release. Therefore, developing titanium implants that combine anti-inflammatory functions with long-lasting sustained-release properties is of great significance.
[0003] White peony root, a traditional Chinese medicinal herb, contains paeoniflorin, a core component that has been proven to have significant anti-inflammatory, antioxidant, and immunomodulatory functions. It can reduce inflammatory responses and promote tissue repair by inhibiting pathways such as NF-κB. However, paeoniflorin is easily degraded by pH in the physiological environment, and its oral bioavailability is low (only about 3-5%), which limits its clinical application. Summary of the Invention
[0004] The technical problem to be solved by this invention is how to effectively alleviate postoperative inflammation of titanium implants and significantly improve osseointegration efficiency.
[0005] The present invention solves the above-mentioned technical problems through the following technical means:
[0006] The first aspect of this invention provides a method for preparing a titanium implant loaded with paeoniflorin liposomes, comprising the following steps: a titanium sheet is subjected to anodizing, acid etching, and oxygen plasma treatment to obtain porous titanium; the porous titanium is then immersed in a dopamine hydrochloride solution to react and obtain a polydopamine titanium sheet; DPPC, cholesterol, DSPE-PEG-NH2, and a paeoniflorin solution are subjected to a thin-film hydration method to obtain paeoniflorin-loaded liposomes; the liposomes are reacted with the dopamine hydrochloride solution via a Michael addition reaction to obtain a liposome polymer; finally, the polydopamine titanium sheet is immersed in the liposome polymer and reacted in the dark to obtain a titanium implant loaded with paeoniflorin liposomes.
[0007] Beneficial effects: This invention combines the active ingredient paeoniflorin from authentic medicinal herbs with the sustained-release properties of liposome nanocarriers, providing a new strategy for the surface functionalization of titanium implant materials, which can improve postoperative anti-inflammatory effects and bone integration efficiency.
[0008] This invention enables the formation of fine pores on the surface of titanium sheets through anodizing, and further expands the pore size through acid etching, so that micron-sized pores can be formed on the surface of the titanium sheets, while also increasing the depth of the pores; then the titanium sheets are treated with oxygen plasma to improve the hydrophilicity of the titanium sheets, so that they can be loaded with more polydopamine and liposome polymers.
[0009] This invention utilizes liposomes as nanocarriers to encapsulate the unstable paeoniflorin. A phospholipid bilayer protects paeoniflorin from degradation under physiological conditions, while simultaneously enabling targeted and timed release at the target site, thus improving drug utilization and efficacy. By encapsulating paeoniflorin within liposomes and utilizing the biomimetic membrane properties of polydopamine molecules to immobilize the paeoniflorin-loaded liposomes within micron-sized pores on a porous titanium surface, the acid-base instability of paeoniflorin is protected, and the photothermal mechanism of polydopamine molecules facilitates the responsive release of paeoniflorin in inflammatory environments.
[0010] Preferably, the DC voltage for anodizing is 55-65V, and the anodizing time is 1 hour.
[0011] Preferably, the acid used for etching is a mixture of 37% hydrochloric acid and 98% concentrated sulfuric acid in a volume ratio of 1:1.
[0012] Preferably, the acid etching is carried out in a water bath at 80°C for 30 minutes.
[0013] Preferably, the oxygen plasma treatment time is 10 minutes and the oxygen plasma treatment power is 50W.
[0014] Preferably, the oxygen flow rate for oxygen plasma treatment is 18–20 sccm, and the pressure for oxygen plasma treatment is 18–20 mTorr.
[0015] Preferably, the reaction temperature is 37°C and the reaction time is 24 hours.
[0016] Preferably, the molar ratio of DPPC, cholesterol, and DSPE-PEG-NH2 is 10:1:0.5.
[0017] Preferably, DPPC, cholesterol, and DSPE-PEG-NH2 are reacted in an organic solvent, and the organic solvent is chloroform.
[0018] Preferably, the Michael addition reaction is carried out in the dark at a temperature of 37°C for 2 hours.
[0019] Preferably, the temperature for the light-protected reaction is 37°C, and the reaction time is 2 hours.
[0020] Preferably, the dopamine hydrochloride solution is obtained by dissolving dopamine hydrochloride in Tris-HCl solution, and the concentration of the dopamine hydrochloride solution is 2 mg / mL.
[0021] A second aspect of the present invention provides a titanium implant loaded with paeoniflorin liposomes, which is prepared according to the above-described method for preparing a titanium implant loaded with paeoniflorin liposomes. Attached Figure Description
[0022] Figure 1 This is a flowchart of the preparation method of the titanium implant loaded with paeoniflorin liposomes according to an embodiment of the present invention;
[0023] Figure 2 These are scanning electron microscope images of the titanium sheet (a), anodized titanium sheet (b), acid-etched titanium sheet (c), and directly acid-etched titanium sheet (d) in Example 1 of the present invention.
[0024] Figure 3 These are scanning electron microscope images of the paeoniflorin-loaded liposomes (a), liposome polymers (b), polydopamine titanium sheets (c), and titanium implants loaded with paeoniflorin liposomes (d) in Example 1 of the present invention.
[0025] Figure 4 This is a schematic diagram of drug release from the titanium implant loaded with paeoniflorin liposomes prepared in Example 1 of the present invention;
[0026] Figure 5 These are atomic force micrographs of titanium sheet (a), anodized titanium sheet (b), acid-etched titanium sheet (c), and directly acid-etched titanium sheet (d) in Example 1 of the present invention.
[0027] Figure 6 This is a bar chart of the contact angles of the titanium sheet, the acid-etched titanium sheet, and the porous titanium in Embodiment 1 of the present invention. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.
[0030] Unless otherwise specified in the embodiments, the techniques or conditions described in the literature in this field or in accordance with the product manual may be followed.
[0031] Example 1
[0032] according to Figure 1 As shown, this embodiment provides a titanium implant loaded with paeoniflorin liposomes and its preparation method, as detailed below:
[0033] (1) Preparation of polydopamine peptide tablets
[0034] Titanium sheets with a purity of 99.99% were sequentially cleaned with acetone, ethanol, and deionized water, 5 minutes each time; then cleaned in a 400W ultrasonic cleaner for 5 minutes, and air-dried to obtain clean titanium sheets. The scanning electron microscope image of the clean titanium sheets is shown below. Figure 2 As shown in (a).
[0035] Clean titanium sheets were immersed in an electrolyte solution and anodized for 1 hour at a DC voltage of 60V. The electrolyte solution consisted of ammonium fluoride, deionized water, and ethylene glycol, with each 100mL of electrolyte containing 0.55g of ammonium fluoride, 5mL of deionized water, and 95mL of ethylene glycol. The sheets were then cleaned with acetone, ethanol, and deionized water solution for 5 minutes each time, followed by ultrasonic cleaning at 160W for 5 minutes. After air drying, the anodized titanium sheets were obtained. The scanning electron microscope image of the anodized titanium sheets is shown below. Figure 2 As shown in (b), the surface of the anodized titanium sheet exhibits uniformly small pores with a diameter of approximately 100 nm.
[0036] Anodized titanium sheets were immersed in acid for etching in a water bath at 80°C for 30 minutes. The acid was a mixed acid solution prepared by mixing 37% hydrochloric acid and 98% concentrated sulfuric acid in a 1:1 volume ratio. The sheets were then cleaned twice using a 160W ultrasonic cleaner for 10 minutes each time, and finally dried in a 37°C oven to obtain the etched titanium sheets. An electron scanning microscope image of the etched titanium sheets is shown below. Figure 2 As shown in (c), the surface of the acid-etched titanium sheet exhibits micron-sized pores, with a pore size of approximately 1000 nm.
[0037] The acid-etched titanium sheet was treated in oxygen plasma for 10 minutes. The power of the oxygen plasma treatment was 50W, the oxygen flow rate was 18sccm, and the pressure was 18.2mTorr, resulting in porous titanium.
[0038] Porous titanium was immersed in a 2 mg / mL dopamine hydrochloride solution, which was obtained by dissolving dopamine hydrochloride in a Tris-HCl solution with a pH of 8.5 and a concentration of 10 mM. The reaction was carried out for 24 hours in a shaker at 37°C and 120 rpm. The titanium was then washed five times with deionized water for 10 seconds each time, and dried in a 37°C oven to obtain polydopamine titanium sheets. Scanning electron microscopy of the polydopamine titanium sheets was performed as follows: Figure 3 As shown in (c), many polydopamine microspheres can be seen tightly attached to the micron-sized pores on the surface of the titanium sheet.
[0039] (2) Preparation of liposome polymers
[0040] 10 mg of dipalmitoylphosphatidylcholine (DPPC, CAS: 63-89-8, molecular weight: 734.04), 0.5 mg of cholesterol (CAS: 57-88-5, molecular weight: 386.6535), and 2 mg of distearylphosphatidylethanolamine-polyethylene glycol-amino (DSPE-PEG-NH2, molecular weight: 2742) were added to 10 mL of chloroform and stirred for 10 min to fully dissolve them to obtain a mixed solution. The mixed solution was poured into an evaporating flask and evaporated under vacuum in a 60 °C water bath for 3 h. The water bath was removed and the reaction was continued under vacuum for 1 h.
[0041] Then, 10 mL of a 10 μg / mL paeoniflorin solution was added to the evaporation flask. The solution was first dissolved by rotation in a 37°C water bath for 5 min, then sonicated for 3 min using a 160W ultrasonic cleaner, and finally dissolved by rotation in a 37°C water bath for 5 min to obtain crude liposome solution. Using G10 dextran gel purification centrifuge tubes, the crude liposome solution was first centrifuged at 3000 rpm and 4°C for 10 min, then centrifuged at 14000 rpm and 4°C for 40 min to obtain liposome precipitate. Finally, the liposome precipitate was resuspended in PBS buffer (pH 7.2-7.4, 0.01 M), centrifuged at 14000 rpm and 4°C for 40 min, the supernatant was discarded, and the precipitate was dissolved in PBS buffer to obtain the paeoniflorin-loaded liposome solution. The scanning electron microscope image of the paeoniflorin-loaded liposome solution is shown below. Figure 3 As shown in (a), liposomes loaded with paeoniflorin with an average diameter of about 30 nm can be seen.
[0042] A 2 mg / mL dopamine hydrochloride solution was slowly added to the liposome-loaded paeoniflorin solution. The reaction was carried out at 37°C and 120 rpm in the dark for 2 hours to obtain the reaction solution. The reaction solution was centrifuged at 14000 rpm and 4°C for 30 minutes to obtain a precipitate. The precipitate was resuspended in PBS buffer and centrifuged again at 14000 rpm and 4°C for 30 minutes to obtain another precipitate. Finally, the precipitate was resuspended in PBS buffer to obtain the liposome polymer solution. A scanning electron microscope image of the liposome polymer solution is shown below. Figure 3 As shown in (b), polydopamine microspheres and liposome microspheres loaded with paeoniflorin are tightly connected together to form liposome polymers.
[0043] (3) Preparation of titanium implants loaded with paeoniflorin liposomes
[0044] Polydopamine titanium sheets were immersed in a liposome polymer solution and reacted in a shaker at 37°C and 120 rpm for 2 hours in the dark. The reacted titanium sheets were then washed with PBS buffer solution to obtain a titanium implant loaded with paeoniflorin liposomes. A scanning electron microscope image of the paeoniflorin-loaded titanium implant is shown below. Figure 3 As shown in (d), the liposome polymer is tightly connected to the polydopamine microspheres in the micron-sized pores of the titanium sheet, further filling the micron-sized pores on the surface of the titanium sheet.
[0045] The titanium implant loaded with paeoniflorin liposomes in this embodiment underwent a drug release test as follows: The titanium implant loaded with paeoniflorin liposomes prepared in this embodiment was immersed in PBS solution at 37°C. An 808nm infrared light source was fixed 2cm directly above the liquid surface, the power switch was turned on, and irradiation was carried out continuously for 3 minutes. The specific results are as follows: Figure 4 As shown, the paeoniflorin standard solution continuously decomposed in PBS solution at 37°C. Furthermore, paeoniflorin was successfully released from titanium implants containing paeoniflorin liposomes after infrared light irradiation, while it was not released from titanium implants containing paeoniflorin liposomes that had not undergone infrared light irradiation. This indicates that encapsulation of paeoniflorin within liposomes protects its stability under physiological conditions and enables its responsive release in inflammatory environments through a photothermal mechanism.
[0046] Comparative Example 1
[0047] This comparative example provides a titanium implant loaded with paeoniflorin liposomes and its preparation method. The difference between this comparative example and Example 1 is that the titanium sheet was not anodized but directly immersed in acid for etching, resulting in a directly etched titanium sheet. The scanning electron microscope image of the directly etched titanium sheet is shown below. Figure 2As shown in (d), the surface of the titanium sheet after direct acid etching is mostly irregular grooves, and it is impossible to form micron-sized pores.
[0048] according to Figure 5 As shown, the Ra value represents the depth of pores on the surface of different titanium sheets; the larger the Ra value, the deeper the pore depth. According to... Figure 2 and 5 It can be seen that the titanium sheet after acid etching in Example 1 has the deepest pore depth. Therefore, the titanium sheet after acid etching in Example 1 has a microporous structure that is more suitable for attaching polydopamine and liposome polymers.
[0049] Comparative Example 2
[0050] This comparative example provides a titanium implant loaded with paeoniflorin liposomes and its preparation method. The difference between this comparative example and Example 1 is that the titanium sheet was not treated with oxygen plasma, but was directly immersed in a hydrochloric acid dopamine solution and reacted in a shaker at 37°C and 120 rpm for 24 hours.
[0051] according to Figure 6 It can be seen that the contact angle of the titanium sheet and the acid-etched titanium sheet is relatively large, and therefore the hydrophilicity is poor; while the porous titanium in Example 1 has the smallest contact angle and the best hydrophilicity, which is conducive to the adhesion of polydopamine and liposome polymers to the surface of the titanium sheet.
[0052] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a titanium implant loaded with paeoniflorin liposomes, characterized in that, Includes the following steps: Porous titanium was obtained by anodizing, acid etching, and oxygen plasma treatment of titanium sheets. The porous titanium was then impregnated in a dopamine hydrochloride solution to obtain polydopamine titanium sheets. DPPC, cholesterol, DSPE-PEG-NH2, and paeoniflorin solution were used to obtain paeoniflorin-loaded liposomes via a thin-film hydration method. The liposomes were then reacted with dopamine hydrochloride solution via a Michael addition reaction to obtain a liposome polymer. Finally, the polydopamine titanium sheets were impregnated in the liposome polymer and reacted in the dark to obtain a titanium implant loaded with paeoniflorin liposomes.
2. The method for preparing a titanium implant loaded with paeoniflorin liposomes according to claim 1, characterized in that, The DC voltage for anodizing is 55–65V, and the anodizing time is 1 hour.
3. The method for preparing a titanium implant loaded with paeoniflorin liposomes according to claim 1, characterized in that, The acid used for etching is a mixture of 37% hydrochloric acid and 98% concentrated sulfuric acid in a 1:1 volume ratio.
4. The method for preparing a titanium implant loaded with paeoniflorin liposomes according to claim 1, characterized in that, The oxygen plasma treatment time was 10 minutes, and the oxygen plasma treatment power was 50W.
5. The method for preparing a titanium implant loaded with paeoniflorin liposomes according to claim 1, characterized in that, The molar ratio of DPPC, cholesterol, and DSPE-PEG-NH2 is 10:1:0.
5.
6. The method for preparing a titanium implant loaded with paeoniflorin liposomes according to claim 5, characterized in that, DPPC, cholesterol, and DSPE-PEG-NH2 react in an organic solvent, namely chloroform.
7. The method for preparing a titanium implant loaded with paeoniflorin liposomes according to claim 1, characterized in that, The Michael addition reaction was carried out in the dark at a temperature of 37°C for 2 hours.
8. The method for preparing a titanium implant loaded with paeoniflorin liposomes according to claim 1, characterized in that, The reaction was carried out at a temperature of 37°C and for 2 hours in the dark.
9. The method for preparing a titanium implant loaded with paeoniflorin liposomes according to claim 1, characterized in that, The dopamine hydrochloride solution is obtained by dissolving dopamine hydrochloride in Tris-HCl solution, and the concentration of the dopamine hydrochloride solution is 2 mg / mL.
10. A titanium implant loaded with paeoniflorin liposomes, characterized in that, The titanium implant loaded with paeoniflorin liposomes was prepared according to any one of claims 1-9.